Enhancing the electrochromic performance of conjugated polymers using thermal nanoimprint lithography. Issue 77 (20th October 2017) - Neo, Wei Teng; Li, Xue; Chua, Soo-Jin; Ling Chong, Karen Siew; Xu, Jianwei
Abstract : Thermal nanoimprinting is employed to create nanopatterned electrochromic conjugated polymer films, giving superior color-changing properties compared to a reference device. Abstract : Thermal nanoimprint lithography was utilized as an efficient method to directly create periodic nanostructures on the conjugated polymer films that were synthesized from 2, 5-bis(2-octyldodecyl)-3, 6-di(thiophen-2-yl)-2, 5-dihydropyrrolo[3, 4- c ]pyrrole-1, 4-dione, 3, 3-bis((tetradecyloxy)methyl)-3, 4-dihydro-2 H -thieno[3, 4- b ][1, 4]dioxepine and thieno[3, 2- b ]thiophene monomers. This type of nanopatterned polymer film with 275 nm features was achieved by the use of a direct, top-down thermal nanoimprinting method, and then fabricated into absorption/transmission type electrochromic devices. The nanopatterned devices displayed considerably better overall electrochromic performance than their non-nanostructured pristine counterpart as evidenced by the improvement of up to 20% in switching speed, coloration efficiency as well as enhanced colored-to-transmissive optical contrast. The improvement in electrochromic performance could be ascribed to the increased exposed polymer surface area induced upon nano-structuring of the conjugated polymer films, which was demonstrated by the fact that the increase in the imprint depth from 100 to 130 nm led to a further improvement in the electrochromic performance such as shorter switching speeds and higher coloration efficiency. In addition, unlike the pristine un-patterned polymer film which displays an identical hue regardless of the viewing angle, the nanoimprinted films gave different hues under different viewing angles because of the ability of the nanogratings to diffract ambient white light, potentially opening up the path to many interesting applications.